2018
DOI: 10.3390/ijerph15102212
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiology of Transition into Adulthood of Rare Diseases Patients: Results from a Population-Based Registry

Abstract: Background: Despite the fact that a considerable number of patients diagnosed with childhood-onset rare diseases (RD) survive into adulthood, limited information is available on the epidemiology of this phenomenon, which has a considerable impact both on patients’ care and on the health services. This study describes the epidemiology of transition in a population of RD patients, using data from the Veneto Region Rare Diseases Registry (VRRDR), a web-based registry monitoring since 2002 a consistent number of R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 43 publications
1
17
1
1
Order By: Relevance
“…In order to provide as robust an estimate as possible, only diseases with prevalence as an epidemiological indicator were selected, and using prevalence values from a wide geographic area were incorporated. While our resulting estimate of 3.5-5.9% does seem high compared to the 0.6% for the Veneto region derived from 331 disorders and groups of disorders from which some prevalent diseases (i.e., cystic fibrosis) are excluded [8], higher figures have been reported in other countries. Walker et al [9] and Chiu et al [10] report prevalences of 2% in Western Australia and 1.5% in Hong Kong respectively, using linked hospital data capture of 467 diseases of the >6000 rare diseases on Orphanet.…”
Section: To the Editorcontrasting
confidence: 81%
“…In order to provide as robust an estimate as possible, only diseases with prevalence as an epidemiological indicator were selected, and using prevalence values from a wide geographic area were incorporated. While our resulting estimate of 3.5-5.9% does seem high compared to the 0.6% for the Veneto region derived from 331 disorders and groups of disorders from which some prevalent diseases (i.e., cystic fibrosis) are excluded [8], higher figures have been reported in other countries. Walker et al [9] and Chiu et al [10] report prevalences of 2% in Western Australia and 1.5% in Hong Kong respectively, using linked hospital data capture of 467 diseases of the >6000 rare diseases on Orphanet.…”
Section: To the Editorcontrasting
confidence: 81%
“…Therefore, from our point of view, the figure yielded by the authors' comprehensive approach (~3.5-5.9%), not only would not be underestimated (as pointed out in the manuscript) but it seems to be overestimated. It is considerably higher than, e.g., the data provided by the Italian population register of the Veneto region (with >15-year of experience), which estimated that 0.61% of its population suffers from one of the RDs they were monitoring (58% of total included in Orphanet) [10].…”
Section: To the Editormentioning
confidence: 73%
“…Our results also indicated that the transition to an adult internal medicine department is not easy at this time in Japan. In fact, this issue has been observed in not only Japan but also other countries [ 24 ] and for not only PKU patients but also patients with other rare diseases [ 25 ]. The explanation for this finding is that internal medicine physicians for adults have little knowledge of PKU or are unable to appropriately treat this disease.…”
Section: Discussionmentioning
confidence: 99%